2018
DOI: 10.1002/jcc.25185
|View full text |Cite
|
Sign up to set email alerts
|

Nature of hydration shells of a polyoxy‐anion with a large cationic centre: The case of iodate ion in water

Abstract: The structural nature of the solvation shells of an iodate ion, which is known to be a polyoxy-anion with a large cationic centre, is investigated by means of Born-Oppenheimer molecular dynamics (BOMD) simulations using BLYP and the dispersion corrected BLYP-D3 functionals. The iodate ion is found to have two distinct solvation regions around the positively charged iodine (iodine solvation shell or ISS) and the negatively charged oxygens (oxygen solvation shell or OSS). We have looked at the spatial, orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 68 publications
(99 reference statements)
1
27
0
Order By: Relevance
“…Such a preferred orientation of the polyatomic anion at interfacial region is expected to orient the interfacial water as H-down, as shown in Scheme b. MD simulation suggested that the water hydrating the “cation-like” iodine of IO 3 – orients their H atoms away from the iodine . Therefore, at interface, the water hydrating the iodine (of IO 3 – ) will be H-down oriented and also expected to contribute to the negative Imχ (2) signal around 3250 cm –1 .…”
Section: Resultsmentioning
confidence: 97%
“…Such a preferred orientation of the polyatomic anion at interfacial region is expected to orient the interfacial water as H-down, as shown in Scheme b. MD simulation suggested that the water hydrating the “cation-like” iodine of IO 3 – orients their H atoms away from the iodine . Therefore, at interface, the water hydrating the iodine (of IO 3 – ) will be H-down oriented and also expected to contribute to the negative Imχ (2) signal around 3250 cm –1 .…”
Section: Resultsmentioning
confidence: 97%
“…As with experiments, AIMD simulation results are challenged by demands of realistic access to suitable ranges of space and time (48). Nevertheless, recent developments in both algorithms and computer power have extended that ability, leading to improved information on ion hydration structures (49,50,51,52,53,54,55,56,57). Our presentation here highlights the correspondence between ion hydration structure illuminated by AIMD simulations with available experiment.…”
Section: Bulk Aqueous Referencementioning
confidence: 91%
“…However, in the case of IO 3 − , the relative intensity in the low-frequency region (below 3400 cm −1 ) is increased, pertaining to the strongly H-bonded water in the hydration shell of IO 3 − . 33,38 This has effectively led to increased spectral width as compared to that of bulk HOD (Figure 4c). These changes in the OHstretch spectrum of the hydration shell water, which are in accordance with the structure breaking (ClO 3 − and BrO 3 − ) and making (IO 3 − ) properties of the oxyhalide anions, are in good agreement with the Imχ (2) spectral changes at the corresponding air/water−NaXO 3 interfaces (Figures 2 and 3).…”
mentioning
confidence: 99%